The Influence of Teachersâ Performance in Promoting Effective English Teaching Classroom at State Junior High School - Rosyada, Amrina; Ramadhianti, Agustina (UICELL, 2017)
Promoting effective English teaching classroom is one of the teachersâ concerns which is positive classroom environment for the sake of achieving success in English teaching and learning process. Beyond the presence of the advanced technology and information, teacherâs performance is still the main variable in promoting the effective English teaching classroom. Thus, the research aims at determining the influence of teacherâs performance to promote the effective English teaching classroom in state junior high school. The teacherâs performance focuses in teacherâs personality and teacherâs language. The effective English teaching classroom is measured quantitatively by applying correlational research design. The method conducts several steps as procedures of investigation in analyzing the data, namely: 1) data collection, 2) data analysis, and 3) data interpretation. Engaged by 71 students of eighth grade and 2 English  teachers, findings have shown that there is a significant correlation between teacherâs performance and effective English teaching classroom. The results are hoped to be as teachersâ and studentsâ contributions in establishing their effective English teaching classroom; gaining their confidence and ability to learn; and use knowledge and skills to interact and to fully participate in education.